Tribological properties of Mg/Al–CO3 layered double hydroxide as additive in base oil. (December 2014) - Zhao, D.; Sham, T-K.; Kasrai, M.; Bai, Z.; Zhao, F.
Abstract : The tribological performance of Mg/Al–CO3 –layered double hydroxide (LDHs) nanoparticles in base oil was studied as a sole additive and in combination with zinc dialkyldithiophosphate (ZDDP) at 100°C. Results show that LDHs could improve antifriction and antiwear properties of base oil. The blend with LDHs alone shows better antifriction properties than that of the mixture of LDHs and ZDDP, but the addition of ZDDP helps to stabilise the friction coefficient. Surface analyses have been performed to study the morphology, nanoparticle distribution and chemical species in the tribofilm. The results show that tribofilms contain Mg, Al, C, O, Zn, P and S, and the structure of Mg/Al–CO3 –LDHs changes under shearing stress and this process can help reduce friction coefficient. Thus, LDHs could be chemically incorporated into tribofilm to reduce the polyphosphate chain length originated from ZDDP decomposition resulting in a medium chain polyphosphate, which provides very good wear protection.